(untitled) (Andamios, Revista de Investigación Social, 2026)
Reseña del libro: Ivcovic, M., Zaharijevic, A. y Pudar, G. (Coords.). (2022). Violence and Reflexivity. The Place of Critique in the Reality of Domination. Lexington Books.